Effects of high commodity prices on western Kansas crop patterns and the Ogallala aquifer - Clark, Matthew Ken (Kansas State University, 2009)
The expansion of the biofuels industry, world demand, and various other factors are having a historic impact on the price of grains. These high prices have been creating a large increase in production of many water intensive crops such as corn. As corn is among the most input-intensive crops, this extra production has raised concerns about environmental impacts and pressures on water resources in particular. While water quality has been a longstanding concern in the cornbelt, much of the new production is in nontraditional corn regions including the southeast, the High Plains, and the western states. In these areas, there is mounting concern over depletion of already stressed water supplies. In the High Plains, the chief water source is the Ogallala aquifer, one of the largest water resources in the world that underlies eight states from South Dakota to Texas. The Ogallala has enabled many agricultural industries, such as irrigated crops, cattle feeding, and meat processing, to establish themselves in areas that would not be possible otherwise. A consequence is that the economy of this region has become dependent on groundwater availability. Continued overdrafts of the aquifer have caused a long-term drop in water levels and some areas have now reached effective depletion. This thesis seeks to estimate the impact of the rising commodity prices on groundwater consumption and cropping patterns in the Kansas portion of the Ogallala. The economy of this region is particularly dependent on water and irrigated crops, with more than 3 million head of feeder cattle and irrigated crop revenues exceeding $600 million annually. Sheridan (northwestern Kansas), Seward (southwestern Kansas), and Scott (west central Kansas) counties have been selected as representative case study regions. These counties have a wide range of aquifer levels with Seward having an abundant supply, Sheridan an intermediate supply, and Scott nearing effective depletion. Cropping patterns in these counties are typical of the western Kansas region, with most irrigated acreage being planted to corn and with dominant nonirrigated rotations of wheat-fallow and wheat-sorghum-fallow. A Positive Mathematical Programming (PMP) model was developed and calibrated to land- and water-use data in the case counties for a base period of 1999-2003. The PMP approach produces a constrained nonlinear optimization model that mimics the land- and water- allocation decision facing producers each year. The choice variables in the model are the acreages planted to each of the major crops and the water use by crop. The model was run for each of the case counties. The PMP calibration procedure ensures that the model solutions fall within a small tolerance of the base period observations. Once calibrated, the models were executed to simulate the impacts of the emerging energy demand for crops over a 60-year period. After the baseline projections were found, the model was then run under increased crop prices that reflect the higher prices observed in 2006 and after. The thesis found that under the high price scenario, both irrigated crop production and water application per acre increased significantly during the early years of the simulated period in all modeled counties. The size of the increases depended on the amount of original water available in each county. The increases generally diminished in magnitude toward the end of the simulation period, but led to smaller ending levels of saturated thickness as compared to the base price in all counties. Finally, in two of the three counties, it was observed that initial increases in irrigated crop acres and water application forces a decline in the aquifer such that less water can be applied per acre in the final years of the simulation. This suggests that high commodity prices forces a higher emphasis on early production levels than later production levels. Additionally, the higher prices have a significant effect on the rate of decline of the Ogallala aquifer.
Keywords: Commodity Prices; Ogallala Aquifer; Irrigation Rates; Crop Patterns; Agriculture, Agronomy (0285); Agriculture, General (0473); Economics, Agricultural (0503)